Nature based Tourism, Opportunities of Indigenous Women and Their Empowerment: A North East Indian Perspective - DE, UTPAL KUMAR (ITB Journal Publisher, LPPM ITB, 2012)
The trade-off between economic development and the environmental quality is a wellknown phenomenon. Till a nation become very highly developed and learn how to manage environment or critical natural resources while undertaking various developmental socio-economic activities the growth process becomes unsustainable. Hence a debate has always been there in regard to the sustainability of the growth process and the preservation of natural resources and maintaining inter-generational as well as intra-generational equity. It is found that the poorer especially the indigenous people, whose livelihood are highly dependent on the natural resource extraction are the worst victim of the natural resource degradation that are caused by the socio-economic activities undertaken by the state as well the richer section of any society. Hence, there is a strong inter-linkage between social and economic activity, sustainability of the resource use and environmental quality. In the context of aforesaid background, nature based tourism that has been one of the fastest growing economic activities in the world during past few decades can be a better option for the maintenance of sustainable welfare along with the preservation of natural wealth. Ecotourism has thus become a buzzword of the time. The indigenous people especially the women have been found to be involved in selling a large number of handloom and handicrafts product that has been prepared from the locally collected minor forest products. Moreover, the development of scope of employment and income in the growing hospitality sector and transport business with the growing demand by the nature loving tourists has created an opportunity for sustainable environmental management at the regional level for the livelihood itself. This paper tries to explore how a substantial section of indigenous population of North East India manage their livelihood through the growing nature based tourism activities through the maintenance of nature itself. Not only that the women who are involved in such activities are empowered in their indigenous rural set up. It is examined on the basis of empirical observation through a primary survey conducted in three prime tourist sites in Meghalaya, the areas of highest rainfall zone in the world. The pleasant climate and the beauty of natural forest are the prime attractions of the visitors over the years.